Industrial Training Report: Pahang Skills Library / Siti Nursyafirah Addawiyyah Shuib - Shuib, Siti Nursyafirah Addawiyyah (Faculty of Information Management, 2018)
I choose Pahang Skills library as a place for my industrial training after successful completed studying for 6 semesters in UiTM Kampus Rembau in Bachelor of Information Science (Hons) Library Management. I started the industrial training on Ith August 2018 until 31st December 2018 which means I will undergo 5 month of internship. There reason why I am choosing this organization because it is a technical college that will give me a new knowledge beside the library knowledge. Moreover, I also can apply the knowledge that I learn during study to settle up the task given. Through this industrial training experience, I have learning the real situation to be a librarian. Lastly, after facing many challenges, problems and barrier, I am becoming a better person which never give up and always find a solution when have a problem.